2015
DOI: 10.1177/2156587214568668
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Randomized Placebo-Controlled Feasibility Study Evaluating Individualized Homeopathy in Managing Pain of Knee Osteoarthritis

Abstract: Clinical Trials Registry, India (CTRI/2014/05/004589).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Even more recently, Sarkar et al 15 reported that Homeopathic remedy Guaiacum officinale possesses antirheumatic and antioxidant activity in experimental animal model and these activities may be more significant in higher potencies. On the other hand, Koley et al, 16 in a double-blinded randomized placebo-controlled study, evaluating individualized Homeopathy in managing pain in knee osteoarthritis (using various Homeopathic remedies— Bryonia alba, Rhus toxicodendron, Calcarea carbonica, A montana , and Natrum muriaticum ), did not find statistically significant differences to justify the superiority of Homeopathic treatment in comparison with placebo.…”
Section: Discussionmentioning
confidence: 97%
“…Even more recently, Sarkar et al 15 reported that Homeopathic remedy Guaiacum officinale possesses antirheumatic and antioxidant activity in experimental animal model and these activities may be more significant in higher potencies. On the other hand, Koley et al, 16 in a double-blinded randomized placebo-controlled study, evaluating individualized Homeopathy in managing pain in knee osteoarthritis (using various Homeopathic remedies— Bryonia alba, Rhus toxicodendron, Calcarea carbonica, A montana , and Natrum muriaticum ), did not find statistically significant differences to justify the superiority of Homeopathic treatment in comparison with placebo.…”
Section: Discussionmentioning
confidence: 97%
“…x1000, x10000 or x100000 (Milgrom 2006). Usually such a little quantity apparently doesn't (Koley et al, 2015;Milgrom 2006). In case of complications after the treatment with Homeopathic medicines either orthologist or family physician that there was no significant difference in complications (Chisquare = 3.036, p=0.081).…”
Section: Discussionmentioning
confidence: 97%
“…in the treatment of low back pain due to osteoarthritis [ 44 ] or an individualised approach, i.e. in the pain management in osteoarthritis of the knee [ 45 ].…”
Section: Discussionmentioning
confidence: 99%